Artikel Review: â€œKondisi Terkini Kualitas Air Sungai Di Daerah Istimewa Yogyakartaâ€ - Nurfadilah; Luthfiah, Zakia Deliana; Perwitasari (Jurnal Pengendalian Pencemaran Lingkungan (JPPL), 2024)
Domestic waste and heavy metals are common problems found in river water. Household activities around the river contribute domestic waste to the river. Also, due to industrial activities in the last few centuries caused heavy metal pollution. This article discusses the quality of Bogowonto, Winongo, Code, Gajah Wong, Opak, Belik and Bedog rivers for the analysis of domestic waste parameter values, while the heavy metal content for Bogowonto and Code river was excluded. The analysis method is purposive sampling and composite sample. The rescent research result on the observation of various parameters showed a fairly high waste content for domestic waste with BOD (Biochemical Oxygen Demand) parameters,while the highest pollution content for heavy metal waste is lead and iron.